Effect of dietary supplementation of jujube fruit (Ziziphus jujuba) powder on performance, some biochemical parameters, and egg quality in quails (Coturnix coturnix japonica) - Eroglu, M.; Ciftci, M.; Simsek, U. G.; Akarsu, S.; Arslan, S.; Hames, M. A.; Mutlu, M. (Polska Akad Nauk, Polish Acad Sciences, Univ Warmia & Mazury Olsztyn, 2024)
This study aimed to evaluate the effects of different dietary supplementation levels with jujube fruit powder on the performance, biochemical parameters, and egg quality characteristics of laying quails. A total of 60 quails (45 days old) were randomly assigned to treatments with different levels of jujube fruit powder: a basal diet (control) and diets supplemented with 5 g/kg (T1), 10 g/kg (T2), with five replicates per treatment (20 quails/treatment and four quails/replicate). The differences between 1-15 and 16-30 days for feed intake (p<0.05), 1-60 days for egg production (p<0.05), 16-30 days for egg weight (p<0.05), and 1-15 and 1-60 days for feed conversion ratio were statistically significant. The highest values for egg width (p<0.01) and egg length (p<0.05) were found in the control group (25.87 and 33.55 mm), while lower values were observed in the T1 and T2 groups. There was no statistical difference between the groups in egg shape index, shell weight, shell ratio, and shell thickness (p>0.05). The yolk height (p<0.05) and yolk diameter (p<0.01) were statistically significant. The differences between the groups for all serum biochemical parameters were insignificant (p>0.05). According to the results of this study, jujube fruit, a rich energy source, can be used as an alternative supplement in poultry diets with positive effects on egg production and feed conversion ratio.
Keywords: egg; jujube; performance; supplement; quail